The effect of sustained-release CARvedilol in patients with hypErtension and heart failure with preserved ejection fraction: a study protocol for a pilot randomized controlled trial (CARE-preserved HF) - Yoon, Minjae; Park, Sung-Ji; Yoo, Byung-Su; Choi, Dong-Ju (Frontiers in Cardiovascular Medicine, 2024)
Background Although beta-blockers improve clinical outcomes in heart failure with reduced ejection fraction, the benefit of beta-blockers in heart failure with preserved ejection fraction (HFpEF) is uncertain. Global longitudinal strain (GLS) is a robust predictor of heart failure outcomes, and recent studies have shown that beta-blockers are associated with improved survival in those with low GLS (GLS <14%) but not in those with GLS ≥14% among patients with LVEF ≥40%. Therefore, the objective of this trial is to evaluate the effect of sustained-release carvedilol (carvedilol-SR) on the outcome [N-terminal pro-B-natriuretic peptide (NT-proBNP) concentration] in patients with hypertension and HFpEF and will assess the differential effects of these drugs on the outcome, according to the GLS categories. Methods This prospective randomized double-blind multicenter trial (CARE-preserved HF) will include 100 patients with HFpEF from three tertiary hospitals in South Korea. Patients with HFpEF and hypertension aged ≥20 years who have evidence of functional and structural heart disease on echocardiography and elevated natriuretic peptide will be enrolled. Eligible participants will be randomized 1:1 to either the carvedilol-SR group (n = 50) or the placebo group (n = 50). Patients in the carvedilol-SR group will receive 8, 16, 32, or 64 mg carvedilol-SR once daily for 6 months, and the dose of carvedilol will be up-titrated at the discretion of the treating physicians. The primary efficacy outcome was the time-averaged proportional change in N-terminal pro-B-natriuretic peptide concentration from baseline to months 3 and 6. We will also evaluate the differential effects of carvedilol-SR on primary outcomes according to GLS, using a cut-off of 14% or the median value. Discussion This randomized controlled trial will investigate the efficacy and safety of carvedilol-SR in patients with HFpEF and hypertension. Clinical Trial Registration ClinicalTrial.gov, identifier NCT05553314.